Exchange rate volatility and foreign direct investment inflows in Brazilian pulp and paper industry - Naumanen, Hanna-Lotta (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
The impact of exchange rate uncertainty on foreign direct investment flows is an open question that has interested researchers for decades after the collapse of Bretton-Woods system and increase in global foreign direct investments. In the investment literature it has often been assumed that increasing uncertainty is detrimental to capital accumulation of firms. However, despite of the extensive literature on the impact of exchange rates on investments and advances in modeling of investment decisions, the results of empirical studies have remained ambiguous. This thesis examines FDI inflows into Brazilian pulp and paper industry in the framework of the real options theory. The real options theory suggests that uncertainty leads to investment delays, and thus when uncertainty in exchange rates increases, the investment flows are expected to decrease. The objective of this thesis was to test whether the real options model accurately describes investment behavior in the pulp and paper sector when the firms face increasing exchange rate uncertainty. In addition, the aim was to find out whether there is a difference in the investment response under the exchange rate uncertainty between the pulp and paper sector and the other sectors of the Brazilian economy. The FDI data was obtained from the database of the Central Bank of Brazil. The data covers years 1999-2015 and the FDI flows were regressed on exchange rate level and exchange rate volatility, measured as the standard deviation of the logarithm of the monthly changes in US dollars to Brazilian real exchange rate. Variables were transformed into logarithms and the estimation was conducted using the ordinary least squares. Logarithms of monthly wage and GDP were added as an additional explanatory variable in two alternative specifications. The results revealed that the impact of exchange rate volatility varied across the categories. The findings of this thesis suggest that direct investments in some sectors are less affected by the exchange rate volatility than others. The positive impact of exchange rate volatility on FDI in primary production category in particular is at odds with the predictions based on the real options theory. These results also contradict some previous studies that have found the impact of exchange rate uncertainty to be detrimental for FDI flows.

Valuuttakurssin epävakauden vaikutus ulkomaisiin suoriin sijoituksiin on avoin kysymys, joka on kiinnostanut tutkijoita jo vuosikymmeniä Bretton-Woods järjestelmän hajottua sekä ulkomaisten suorien sijoitusten määrän kasvettua globaalissa taloudessa. Investointeja käsittelevässä kirjallisuudessa lisääntyvän epävakauden on usein oletettu olevan haitallista yrityksille. Laajasta aihetta käsittelevästä kirjallisuudesta sekä investointimallien kehityksestä huolimatta empiiriset tulokset valuuttakurssien vaikutuksista investointeihin ovat jääneet ristiriitaisiksi. Tämä tutkimus tarkastelee Brasilian sellu- ja paperituotantoon suunnattuja ulkomaisia suoria sijoituksia reaalioptioteorian näkökulmasta. Reaalioptioteorian mukaan lisääntyvä epävakaus johtaa investointien lykkäämiseen, ja näin ollen valuuttakurssien epävakauden voi odottaa johtavan investointien laskuun. Tutkimuksen päämääränä on selvittää, selittääkö reaalioptioteoria investointikäyttäytymistä paperi- ja sellutuotannon alalla, kun yritykset kohtaavat kasvavaa valuuttakurssin epävakautta. Lisäksi tavoitteena oli selvittää, onko valuuttakurssin volatiliteetin vaikutus investoinneille sama paperi- ja sellutuotannossa sekä muilla Brasilian talouden sektoreilla. Ulkomaisia suoria sijoituksia koskeva aineisto on saatu Brasilian keskuspankin tietokannasta. Aineisto kattaa vuodet 1999-2015, ja investointeja selittävinä muuttujina käytettiin Yhdysvaltain dollarin kurssia Brasilian realeissa ilmaistuna sekä valuuttakurssin volatiliteettia mitattuna keskihajonnalla valuuttakurssin kuukausitason muutoksista. Muuttujat muutettiin logaritmimuotoon ja estimointi suoritettiin pienimmän neliösumman menetelmää käyttäen. Palkkaa ja bruttokansantuotetta kuvaavat muuttujat sisällytettiin mukaan analyysiin kahdessa vaihtoehtoisessa mallissa. Tulokset osoittavat, että valuuttakurssin volatiliteetin vaikutus investointeihin vaihtelee sektoreittain. Löydökset viittaavat siihen, että joillain aloilla suorat sijoitukset ovat vähemmän herkkiä valuuttakurssin volatiliteetille kuin toisilla aloilla. Erityisesti valuuttakurssin volatiliteetin myönteinen vaikutus alkutuotantosektorilla on ristiriidassa reaalioptioteoriaan pohjaavien ennusteiden kanssa. Nämä tulokset ovat myös ristiriidassa joidenkin aiempien empiiristen tutkimusten kanssa, jotka ovat havainneet valuuttakurssin volatiliteetin olevan haitallista suorille sijoituksille.